2013
DOI: 10.5897/jpbcs13.0403
|View full text |Cite
|
Sign up to set email alerts
|

GGE biplots to analyze soybean multi-environment yield trial data in north Western Ethiopia

Abstract: The study was undertaken with the objective to examine the nature and to quantify the magnitude of genotype x environment interaction effects on soybean [Glycine max (L.) Merr.] grain yield and to determine the winning genotype (s) for test environments in north western Ethiopia. The experiment was executed at four different locations of Ethiopia for two consecutive years (2007 and 2008) using thirty two genotypes including two checks. Randomized complete block design with three replicates was employed. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The results of this study imply that environment and GEI are important in controling the expression of yield trait (Gedif et al, 2014). Similar findings in the same crop were also obtained in various studies (Asfaw et al, 2009;Gurmu et al, 2009;Bueno et al, 2013;Atnaf et al, 2013;Jandong et al, 2011;Bhartiya et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study imply that environment and GEI are important in controling the expression of yield trait (Gedif et al, 2014). Similar findings in the same crop were also obtained in various studies (Asfaw et al, 2009;Gurmu et al, 2009;Bueno et al, 2013;Atnaf et al, 2013;Jandong et al, 2011;Bhartiya et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…GEI is a common phenomenon in a multi-environment yield trials (Hagos and Abbay, 2013), and can be defined as the failure of genotypes to achieve consistent performance (stability) across different environments (Baker, 1988). It has been reported that the GEI may reduces the correlation between phenotype and genotype as well as complicates in breeding program, such as during the testing and selection of superior genotypes (Rao et al, 2011;Atnaf et al, 2013;Hagos and Abbay, 2013;Kumar et al, 2014). The significant presence of GEI has been showed in previous studies in rice (Samonte et al, 2005), sorghum (Rakshit et al, 2010), maize (Tonk et al, 2011), potato (Gedif et al, 2014), and soybean (Kandil et al, 21012;Adie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the AMMI analysis, the first principal component (PCI) and second principal component (PCII) explained 34.06% and 13.49% of the total G×E variation (47.55%), respectively (Table 3). The large G×E effects depicted that the performance of soybean genotypes was different at different locations (Atnaf et al, 2013). The graphical method GGE biplot was employed to approximate and display the GGE of a multi environment trials (MET).The GGE refers to genotypic main effects (G) and G×E interaction (GE) plays a crucial role in cultivar evaluation in multi-locational trials and the GGE biplot has many visual interpretations in comparison to AMMI that particularly allows visualization of any crossovers in the G×E interaction (Karimizadeh et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This 66.73% attributes was Figure 3. The GGE biplot is an effective method for which-won-where pattern and superiorly performing stable genotypes displaying via GEI vs. ME's visualizing (Yan et al, 2007;Atnaf et al, 2013;Massaine et al, 2018). The results of GGE biplot showed that G3, G5, G4, G12, G9, and G10 were the highest and poorest located at the vertexes of polygon responding either positively or negatively for seed yield (Figure 3).…”
Section: Analysis Of Variancesmentioning
confidence: 99%